AVALIAÇÃO PÓS-OCUPAÇÃO EM HABITAÇÃO DE INTERESSE SOCIAL VERIFICAÇÃO DAS CONDIÇÕES DE DIMENSIONAMENTO, ACESSIBILIDADE E CONFORTO PSICOLÓGICO NAS VILAS SÃO PEDRO 1 E 3, EM MACEIÓ, ALAGOAS - Omena, Polyanna; Sampaio, Thaisa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
To guarantee accessibility to housing, it is necessary to promote autonomous mobility conditions. The design of the spaces of Social Interest Housing should be accessible, providing that the house has its functioning both adequate and comfortable. Situations of undersize can represent physical and psychological harm to users. This article aims to verify the conditions of sizing, accessibility and psychological comfort in the residential Vila São Pedro 1 and 3, in the city of Maceió - AL, destined to families benefited with the PAC - Minha Casa Minha Vida. The methodological procedures were based on Post Occupancy Assessment. The documentary searches occurred in the Infrastructure Secretary - AL. The application of questionnaires and the physical analysis occurred in 19 housing units, and followed the parameters recommended by NBR 9050 (ABNT, 2015) and the Manual of Universal Design of Housing of Social Interest (GOVERNO DE SÃO PAULO, 2010). It was verified that the dwellings were inadequate about dimensional and ergonomic aspects, in order to not attend the needs of the residents, the guarantee to the equity and the satisfaction of the users.